2018
DOI: 10.1055/s-0043-123879
|View full text |Cite
|
Sign up to set email alerts
|

Mögliche Einflussfaktoren für die postoperative Visusprognose bei retroiridaler Irisklauenlinsenimplantation

Abstract: The axial length and preoperative VA affect postoperative visual acuity and visual acuity gain significantly. In eyes with lower preoperative visual acuity and in longer eyes larger visual acuity gain can be expected after retroiridal iris claw lens implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Horizontal ovalization of the pupil in the early postoperative phase is observed in a range of 0%-44%. 15 , 17 , 20 , 21 , 23–26 , 28 , 30 , 36–38 , 40–44 , 48–52 , 54–56 This pupil ovalization is mostly temporary and usually pupil dilation is not affected. Toro et al found a temporary (<1 week) pupil ovalization in only 2 (2%) patients.…”
Section: Postoperative Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Horizontal ovalization of the pupil in the early postoperative phase is observed in a range of 0%-44%. 15 , 17 , 20 , 21 , 23–26 , 28 , 30 , 36–38 , 40–44 , 48–52 , 54–56 This pupil ovalization is mostly temporary and usually pupil dilation is not affected. Toro et al found a temporary (<1 week) pupil ovalization in only 2 (2%) patients.…”
Section: Postoperative Outcomesmentioning
confidence: 99%
“…However, studies have shown increased postoperative IOP at a frequency of up to 31%. 14–18 , 20 , 21 , 23–28 , 30 , 31 , 33–52 , 54–56 This rise in IOP could be due to the postoperative inflammation and retained viscoelastic in the early postoperative period. 16–18 , 21 , 26–28 , 54 , 55 Dalby et al and Kristianslund et al found no significant differences in the rate of glaucoma or increased IOP in patients who underwent IOL exchange for retropupillary ICIOLs compared with repositioning of the IOL in late in-the-bag IOL dislocation.…”
Section: Postoperative Outcomesmentioning
confidence: 99%
See 1 more Smart Citation